I/Q Imbalance Compensation for Six-Port Interferometers in Radar Applications - Linz, Sarah; Vinci, Gabor; Lindner, Stefan; Mann, Sebastian; Lurz, Fabian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (European Microwave Conference, 2014)
Six-port interferometers are of great interest for displacement and vibration measurements in industrial as well as medical applications. However, they show offsets as well as amplitude and phase imbalances in their differential in-phase and quadrature signals, leading to inaccuracies of the measured displacement. If a very slow moving or vibrating target has to be monitored, an additional phase shifter for calibration is needed, so that the system’s errors can be compensated. A method for calculation and compensation of errors is presented and a compact and cost-efficient implementation of a phase shifter for 24 GHz Six-port interferometers is shown.
elib2cris::1512001600,linz2014b
Keywords: Six-Port; Ellipse; IQ Imbalance; Interferometer